Neurofunctional maps of the 'maternal brain' and the effects of oxytocin: A multimodal voxel‐based meta‐analysis. Issue 10 (9th June 2014) - Rocchetti, Matteo; Radua, Joaquim; Paloyelis, Yannis; Xenaki, Lida‐Alkisti; Frascarelli, Marianna; Caverzasi, Edgardo; Politi, Pierluigi; Fusar‐Poli, Paolo
<x xml:space="preserve">Abstract</x> Several studies have tried to understand the possible neurobiological basis of mothering. The putative involvement of oxytocin, in this regard, has been deeply investigated. Performing a voxel‐based meta‐analysis, we aimed at testing the hypothesis of overlapping brain activation in functional magnetic resonance imaging (fMRI) studies investigating the mother–infant interaction and the oxytocin modulation of emotional stimuli in humans. We performed two systematic literature searches: fMRI studies investigating the neurofunctional correlates of the 'maternal brain' by employing mother–infant paradigms; and fMRI studies employing oxytocin during emotional tasks. A unimodal voxel‐based meta‐analysis was performed on each database, whereas a multimodal voxel‐based meta‐analytical tool was adopted to assess the hypothesis that the neurofunctional effects of oxytocin are detected in brain areas implicated in the 'maternal brain.' We found greater activation in the bilateral insula extending to the inferior frontal gyrus, basal ganglia and thalamus during mother–infant interaction and greater left insular activation associated with oxytocin administration versus placebo. Left insula extending to basal ganglia and frontotemporal gyri as well as bilateral thalamus and amygdala showed consistent activation across the two paradigms. Right insula also showed activation across the two paradigms, and dorsomedial frontal cortex activation in mothers but deactivation with oxytocin. Significant activation in areas involved in empathy, emotion regulation, motivation, social cognition and theory of mind emerged from our multimodal meta‐analysis, supporting the need for further studies directly investigating the neurobiology of oxytocin in the mother–infant relationship.